PENGELOLAAN AGROEKOSISTEM DENGAN PENDEKATAN ETNOEKOLOGI DI KECAMATAN NAMANG, BANGKA TENGAH - Fellica Fellica; Budi Afriyansyah; Gunawan Gunawan (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2018)
Agroecosystem is form of ecosystem that is man-made.It is a part of ethnoecology as a way for traditional society to cultivate their land for agricultural purposes. The people of Namang Subdistrict has long applied their ancestors tradisional ecology knowledge in culvating their rice fields and gardens. Exploring this knowledge and surpassing it would be beneficial to humankind. To collect the data, the present writer conducted field observation and interview by using snowball sampling method and scientific study. Namang society cultivates rice fields and gardens based on traditional knowladge. Farmer’s rice agroecocystems believe in the moon and the to plant rice is very influential on natural conditions, because nature for them greatly influences the success of rice fields. The murok jerameh tradition is a thanksgiving for the abundant rice yields and begs god that the following year’s harvest is also abundant. Farmers agroecosystems believe that the existence of kiara (Ficus benjamina L) trees indicates that the land is fertile.